Objectively-assessed neighbourhood destination accessibility and physical activity in adults from 10 countries: An analysis of moderators and perceptions as mediators. (August 2018) - Cerin, Ester; Conway, Terry L.; Adams, Marc A.; Barnett, Anthony; Cain, Kelli L.; Owen, Neville; Christiansen, Lars B.; van Dyck, Delfien; Mitáš, Josef; Sarmiento, Olga L.; Davey, Rachel C.; Reis, Rodrigo; et al.
Abstract: Rationale: Residents of neighbourhoods with high destination accessibility (higher population density, more-interconnected streets, and better access to services, public transport and parks) are more physically active. Evidence on the factors that underlie these associations is sparse and inconsistent. Objective: We examined (1) five socio-demographic and four non-destination perceived neighbourhood attributes as moderators of the relationship between objectively-assessed destination accessibility and moderate-to-vigorous physical activity (MVPA); (2) perceived indicators of destination accessibility as mediators of those relationships; and, (3) the generalizability of findings across 14 cities. Methods: Data were from the International Physical Activity and Environment Network (IPEN) Adult study ( N = 6822), which provided comparable objective and perceived environmental variables and accelerometer-based MVPA from 14 cities across 10 countries. Mediation and mediation moderation analyses were performed. Results: Objective net residential density, public transport density, and number of parks in the neighbourhood were consistently associated with MVPA across all examined socio-demographic groups and non-destination perceived neighbourhood characteristics. However, only the association between number of parks and MVPA was mediated by its conceptually-comparable perceived indicator. While the associations of objective intersection density and land use mix with MVPA were moderated by both gender and perceived pedestrian infrastructure/safety, only the latter moderating effects were mediated by the conceptually-comparable perceived indicators. Perceived neighbourhood safety and/or aesthetics moderated the associations of objective ratio of retail/civic land to total area and distance to nearest transport stop with MVPA. These associations were not mediated by the conceptually-comparable perceived indicators. Conclusion: Densely populated neighbourhoods with access to public transport and parks have the potential to significantly and equitably contribute to adults' MVPA on a global scale. Perceived neighbourhood aesthetics, pedestrian-friendliness and safety can magnify the positive effects of mixed-use neighbourhoods on residents' MVPA by interacting with the perceived ease of access to a variety of destinations. Highlights: Objective environment and physical activity (PA) data were collected in 14 cities. Parks, residential and public transport densities were consistent correlates of PA. Few moderation and mediation effects were found in the examined associations. Respondents' perceptions mediated objective land use mix-PA relations. Perceived aesthetics, pedestrian infrastructure and safety were moderators.